Science and Sustainable food Security - Swaminathan, Prof. M.S. (Journal of Soil and Water Conservation, 2022)
The Bengal famine of 1942-43 provided the backdrop to our independence. Gandhiji said in Noakhali in 1946, "God is bread to those who are hungry" and that it is a fundamental duty of free India to ensure that every individual is enabled to earn his./her daily bread. This led Jawaharlal Nehru to pronounce in 1948 that "everything else can wait, but not agriculture."